KETELADANAN KARAKTER TIGA DEWI PADA NASKAH DHADHASARING PUTRI TITIGA BAGI PEREMPUAN JAWA - Sa’idah Harma Putri; Murni Widyastuti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The research entitled Exemplary Basic Characters of the Three Goddesses is a research that contains the presentation of some of the basic characters of three goddesses in the Purwa era, namely Dewi Erawati, Dewi Surtikanti, and Dewi Banuwati in the Dhadhasaring Putri Titiga NB 1091 Manuscript which can be exemplified, especially Javanese women. The discussion about character exemplary based on the basic characters of the three goddesses in the DPT script was chosen because through example it can build the character of Javanese women in improving their quality and building harmony and harmony in life that will continue. The purpose of this study is to explore and explain some of the basic characters of Dewi Erawati, Dewi Surtikanti, and Dewi Banuwati who can be role models for Javanese women. . This research is qualitative research using philological methods and work steps. The results showed that the habits possessed by Dewi Erawati, Dewi Surtikanti, and Dewi Banuwati are basic characters that can be role models for Javanese women. The novelty produced by this study is in the form of a study of the content of the manuscript text regarding the example of the characters possessed by the three goddesses in the manuscript text of Dhasaring Putri Titiga NB 1091, while in the previous research it was carried out only as a need for making a manuscript catalog.